Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/won.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Cohort Study to Assess the Impact of a Silver-Alloy and Hydrogel-Coated Urinary Catheter on Symptomatic Catheter-Associated Urinary Tract Infections

Abstract: PURPOSE:The purpose of this study was to determine the effect of a silver-alloy hydrogel catheter on symptomatic catheter-associated urinary tract infections (CAUTIs).DESIGN:Multicenter before-after non-randomized cohort study.SUBJECTS AND SETTING:Seven acute care hospitals ranging in size from 124 to 607 beds participated in this study. The study population included adult patients with a positive urine culture 2 or more days after admission, who underwent Foley catheterization.METHODS:Catheter-associated urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 8 publications
0
46
2
2
Order By: Relevance
“…A requirement was that the patients enrolled in the study would follow the well-established management flow of care and routines for the specific diagnoses included. There are reports that silicone catheters coated with some noble metals reduce CAUTI in defined hospitalized populations [8][9][10]. The present study could not, however, confirm any advantage of the intervention catheter type in this population of patients.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…A requirement was that the patients enrolled in the study would follow the well-established management flow of care and routines for the specific diagnoses included. There are reports that silicone catheters coated with some noble metals reduce CAUTI in defined hospitalized populations [8][9][10]. The present study could not, however, confirm any advantage of the intervention catheter type in this population of patients.…”
Section: Discussioncontrasting
confidence: 94%
“…Different catheter materials have been studied. Silver alloy urinary catheters have been shown in some studies to reduce bacteriuria and symptomatic UTI [8][9][10]. However, the evidence for any major difference in terms of frequency of bacterial colonization and symptomatic UTI is still poor [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of effect is not surprising due to the short catheterisation time and low-risk patient group. In a more recent multicentre cohort study in 2014, Lederer et al 4 examined the impact of noble metal alloy catheters on symptomatic CA-UTI and antibiotic use based on the NHSN surveillance and concluded that a 58% relative reduction (P<0.0001) in NHSN-defined CA-UTI rate was observed and 60% fewer antibiotics were used when compared with conventional catheters.…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, by prevention of CA-UTI, a significant reduction in morbidity and mortality, as well as the health care economic burden, can be anticipated.…”
Section: 一項前瞻性介入研究以探討銀合金水凝膠塗層導 管對出現導管相關性尿道感染的影響mentioning
confidence: 99%
“…These catheters have been introduced into practice in the US and several studies support their efficacy, safety, and cost-effectiveness. [222324] However, the CAUTI-reducing effect observed in these studies varies considerably, suggesting that the efficacy is highly dependent on patient group characteristics, hospital and/or region, catheterization time period, and which definition of CAUTI has been used.…”
Section: Introductionmentioning
confidence: 99%